THE EFFECT OF WORK STRESS AND FINANCIAL REWARD TOWARDS SALES & MARKETING WORK PERFORMANCE - Anthonius Anthonius (COMPETITIVE, 2022)
The purpose of this research is to focus on examining the effect of work stress and financial rewards towards work performance in the hotel industry in Indonesia. This research employs quantitative research with hypothesis testing. 100 employees in the sales & marketing division in the 5-star hotel industry were used as samples in this study. A questionnaire was used as the research instrument in this study. Structural Equation Modelling (SEM based on covariance) was used to analyse data. The study's findings show that, during the pandemic, financial reward factor has no effect on work performance in the hotel industry's sales and marketing department. However, work stress is a factor that has an impact on job performance.Keywords: work stress, financial reward, work performance, hotel industry